If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 8x + -42 = 66 Reorder the terms: -42 + -2x + 8x = 66 Combine like terms: -2x + 8x = 6x -42 + 6x = 66 Solving -42 + 6x = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 6x = 66 + 42 Combine like terms: -42 + 42 = 0 0 + 6x = 66 + 42 6x = 66 + 42 Combine like terms: 66 + 42 = 108 6x = 108 Divide each side by '6'. x = 18 Simplifying x = 18
| F(x)=-3X^3-2x+4 | | 9x-25=8x-25 | | 20=-5v-5 | | 3w+12=66 | | (k-2)x+(k+4)y+3k^2-8k+5=0 | | 3(x+6)=4x+8 | | abs(5x-4)=abs(3x+6) | | 7x-105+6x=155 | | ((5+(1*(1*(60-43))))-14)*5= | | X^4-5x^3+8x-5x+1=0 | | 24+y+3y=36 | | X^3-14x^2-32x=0 | | 6(5x+9)-6=30x+48 | | -5x-13+18=29 | | 0.67x-5=0.5x-3 | | 1.2x=21 | | n^2+n=20000 | | 12x=3/5 | | -28+10x-8x=10 | | 203+121=x^2 | | 25n+5q=65 | | 4x-6x-18=30 | | -1.33x-0.5=2(0.167x-4) | | 7m-13=15m+8 | | X^16x=0 | | 13x^2+-65x+182=0 | | (2x-6)(x+4)x=0 | | 7(x+4)-8=20 | | 3.3=m-2.2 | | (3x-3)(x+2)=120 | | (2w+6)w=80 | | 8x=-6x-98 |